2015
DOI: 10.1159/000367696
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Tolerability of a Novel Selective Corticosteroid in Atopic Dermatitis - Two Randomised Controlled Trials

Abstract: Topical corticosteroids remain the first-line therapy for atopic dermatitis (AD). Hence, we investigated the efficacy and safety profile of a novel selective corticosteroid, GW870086. We performed 2 randomised, double-blind, controlled studies with 25 AD patients and 20 healthy subjects. The changes in the Three-Item Severity (TIS) score and the skin thickness were the primary end points, respectively. The adjusted TIS score (day 22) shows that the novel corticosteroid resulted in a non-significant, but dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In clinical trials, GW870086 has been studied in an inhaled formula on 36 mild to moderate asthmatics in a Phase II study [64], but no effect compared to placebo was found in change of FEV1. In two different trials investigating atopic dermatitis, a lack of effect was also present [66]. In another study of 136 asthmatics, not yet published, an effect on FEV1 was found in all study arms of patients using GW870086 (clinicaltrials.gov ID: NCT01245426).…”
Section: Competitive Environmentmentioning
confidence: 95%
See 1 more Smart Citation
“…In clinical trials, GW870086 has been studied in an inhaled formula on 36 mild to moderate asthmatics in a Phase II study [64], but no effect compared to placebo was found in change of FEV1. In two different trials investigating atopic dermatitis, a lack of effect was also present [66]. In another study of 136 asthmatics, not yet published, an effect on FEV1 was found in all study arms of patients using GW870086 (clinicaltrials.gov ID: NCT01245426).…”
Section: Competitive Environmentmentioning
confidence: 95%
“…It has been designed and studied aiming for treatment of respiratory [63,64], ophthalmological [65] as well as dermatological [66] diseases. This drug is a classical steroidal molecule, modified at the 17-a position, a feature shared by the relatively newly approved ICS, FF [63].…”
Section: Competitive Environmentmentioning
confidence: 99%
“…Furthermore, overexpression of phosphorylation of ERK, JNK, p38, and p65 may accelerate the AD symptoms [ 8 ]. The current strategies in the treatment of AD include topical application of emollients, corticosteroids, calcineurin inhibitors, phototherapy, oral administration of steroids and immunosuppressants, and biologics [ 9 ]. However, these treatment modalities usually accompanied with side effects and drug tolerance.…”
Section: Introductionmentioning
confidence: 99%